2015
DOI: 10.1016/j.maturitas.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction in the community: A systematic review of case-finding instruments that predict adverse healthcare outcomes in community-dwelling older adults

Abstract: Few case-finding instruments are available to community healthcare professionals. This review aims to identify short, valid instruments that detect older community-dwellers risk of four adverse outcomes: hospitalisation, functional-decline, institutionalisation and death. Data sources included PubMed and the Cochrane library. Data on outcome measures, patient and instrument characteristics, and trial quality (using the Quality In Prognosis Studies [QUIPS] tool), were double-extracted for derivation-validation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 57 publications
2
72
0
3
Order By: Relevance
“…However, prior studies on understanding the course of functional decline have been performed in older populations with a majority of people well above 70 years of age, in whom functional decline was often already present [5]. By focusing on a younger cohort of older people, we will be better able to identify distinct subgroups in the population who may be target groups for preventive interventions.…”
Section: Introductionmentioning
confidence: 99%
“…However, prior studies on understanding the course of functional decline have been performed in older populations with a majority of people well above 70 years of age, in whom functional decline was often already present [5]. By focusing on a younger cohort of older people, we will be better able to identify distinct subgroups in the population who may be target groups for preventive interventions.…”
Section: Introductionmentioning
confidence: 99%
“…b) The CARTS (Community Assessment of Risk & Treatment Strategies) project is a screening and assessment initiative based on an easy to perform riskstratification scale (pre-screen), the Risk Instrument for Screening in the Community (RISC) [35][36][37], and a brief comprehensive geriatric assessment instrument, the Community Assessment of Risk Instrument (CARI) [38]. …”
Section: Caregiversmentioning
confidence: 99%
“…Frailty indicators have been extensively validated in multiple populations for their ability to predict age-related adverse health outcomes ranging from falls to mortality in elderly populations (14). Measures of frailty have been reviewed recently by who showed that different instruments captured different characteristics of frailty and that whether an individual is classified as frail or not depends on the index of frailty used in the assessment (15).…”
Section: Frailty Vs Healthy Ageingmentioning
confidence: 99%